Job Rotation, Teamwork and Employee Performance: The Mediating Role of Work Motivation - Ilham Ilham; Uli Wildan Nuryanto; Andi Hasryningsih Asfar (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: This study aims to analyze the influence of job rotation and teamwork on employee performance through work motivation as a mediating variable at PT. Pelabuhan Cilegon Mandiri. Research Method: The study employed a quantitative approach with a survey method involving 170 employees selected using proportionate stratified random sampling. Results and Discussion: The results of the study showed that job rotation had a positive and significant effect on employee performance (β=0.436; p<0.001) and work motivation (β=0.324; p<0.001). Teamwork also had a positive and significant effect on employee performance (β=0.315; p<0.001) and work motivation (β=0.609; p<0.001). Furthermore, work motivation had a positive and significant effect on employee performance (β=0.230; p<0.001). Work motivation was proven to significantly mediate the effect of job rotation on employee performance and the effect of teamwork on employee performance. All research hypotheses were accepted. Implications: companies need to optimize competency-based job rotation programs, strengthen inter-team collaboration, and create a work environment that fosters motivation as a sustainable strategy for improving employee performance. Originality: testing the relationship model between job rotation and teamwork on employee performance through work motivation as a mediating variable in the context of the port sector